MANAGEMENT SYSTEM OF PESANTREN SAFETY OFFICER FOR LEARNING ORDER - Hakim, Luqmanul (Journal Of Islamic Education And Pesantren, 2021)
The purpose of this study was to determine the implementation of the learning control system in Pondok Pesantren Darussalam Sumbersari Kediri. The orderliness of students' learning can be improved through the boarding school's security management system. This control system relies on the maximum role of Islamic boarding school security staff in the activities and activities that exist in Islamic boarding schools. This study uses a qualitative field method. This research is intended to understand the phenomenon of what is experienced by research subjects, for example behavior, perception, motivation, action, and others related to orderliness of learning in Darussalam Islamic Boarding School and security management systems and security strategies in improving learning order. This study concludes that the system for controlling learning activities at Pondok Pesantren Darussalam Sumbersari Kediri uses a punishment strategy that has value in learning. This punishment is termed takzir. Keywords: safety officer, pesantren, learning order, ta'zir. SISTEM PENGELOLAAN PETUGAS KEAMANAN PESANTREN DALAM KETERTIBAN PEMBELAJARAN Abstrak Tujuan penelitian ini adalah untuk mengetahui implementasi sistem penertiban pembelajaran di Pondok Pesantren Darussalam Sumbersari Kediri. Ketertiban pembelajaran santri dapat ditingkatkan melalui sistem pengelolaan keamanan pondok pesantren. Sistem penertiban ini bertumpu pada peran maksimal staf keamanan pondok pesantren dalam kegiatan dan aktifitas yang ada dipondok pesantren. Penelitian ini menggunakan metode kualitatif lapangan. Penelitian ini dimaksudkan untuk memahami fenomena tentang apa yang dialami oleh subjek penelitian misalnnya perilaku, persepsi, motivasi, tindakan, dan lain-lain berkaitan dengan ketertiban pembelajaran di Pondok Pesantren Darussalam dan sistem pengelolaan keamanan dan strategi keamanan dalam meningkatkan ketertiban pembelajaran. Penelitian ini menyimpulkan bahwa system penertiban kegiatan pembelajaran di Pondok Pesantren Darussalam Sumbersari Kediri menggunakan strategi punishment (hukuman) yang bernilai pembelajaran. Hukuman ini diistilahkan dengan takzir. Kata kunci: petugas keamanan, pondok pesantren, ketertiban pembelaran, takzir.